Perencanaan Arsitektur Teknologi pada PT.X - Kristin Tulasi; Adi Wibowo; Lily Puspa Dewi (Jurnal Infra, 2016)
PT. X is a company that specializes in the production of iron pipe, which has several divisions to run the operations of the company. Currently the company have an information system to support multiple business processes. That existing information systems still has many shortcomings because it is still not well integrated. The information system is only to support the accounting process and  buying and selling process. Other business processes still using the recording using the Microsoft Excel application. Therefore, analysis and design of enterprise architecure for PT. X will be carried out in this paper. That process use Enterprise Architecture Planning framework. Analysis and designing process begins with understanding the company's business model and strategy. After that, it will continue with the comparison condition information technology to the problems and needs of the future information technology in the company. Then it will continue with data architecture, application architecture, and technology architecture design that is consistent with the objectives, strategies, and business processes. The design of data architecture will deliver several company’s sub-systems, such as Purchasing Sub System, Finance and Accounting Sub System, Sales Sub System, Warehouse Sub System, Production Sub Systems, and Personnel Sub System. The design of applications architecture will deliver several applications that support sub-systems that have delivered in data architecture design. The main application is Purchasing Information Systems, Finance and Accounting Information Systems, Sales Information Systems, Warehouse Information Systems, Production Information Systems, and Personnel Information Systems. These applications will be supported by additional applications, such as data provider that serves as a communication tool in the process of exchanging data between applications using a client/server architecture pattern.